1999
DOI: 10.1143/jjap.38.l68
|View full text |Cite
|
Sign up to set email alerts
|

Morphology Evolution of SiO2 Films Deposited by Tetraethylorthosilicate/O3 Atmospheric-Pressure Chemical Vapor Deposition on Thermal SiO2

Abstract: A new structure of piezomotor using a flextensional coupler is proposed. Two longitudinal actuators and an elliptical shell constitute its frame. The basic structure and the operating mode are first presented. The coupling between a translation mode and a flexion mode generates an elliptic motion at shell tops. The design method based on a finite element model and an electromechanical equivalent circuit permits the structure dimensioning. Construction of motor prototypes indicates the reliability of the princi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2001
2001
2005
2005

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 12 publications
1
4
0
Order By: Relevance
“…Physically, the correlations of the noise arise from the coexistence of memory effects and surface heterogeneity during silica CVD growth. 18,19 It is important to stress that these new findings do not invalidate our previous results concerning the CVD silica growth evolution, rather they contribute to a more detailed understanding of such a complex growth process.…”
Section: Introductionsupporting
confidence: 67%
See 1 more Smart Citation
“…Physically, the correlations of the noise arise from the coexistence of memory effects and surface heterogeneity during silica CVD growth. 18,19 It is important to stress that these new findings do not invalidate our previous results concerning the CVD silica growth evolution, rather they contribute to a more detailed understanding of such a complex growth process.…”
Section: Introductionsupporting
confidence: 67%
“…From these data it is evident that both sets of films have both active and passive ͑namely, less active͒ sites, and that the high-temperature set presents a lower concentration of active sites than the low-temperature set. On the other hand, it has been recently reported 18,19 for silica CVD films deposited from tetraethylorthosilicate ͑TEOS͒/ozone precursors that there exist memory effects during growth that influence the final film morphology, in particular, the film surface roughness. These memory effects are related to the existence of surface sites of different activities for deposition, and to the persistence in time of the activity properties for a given site on the substrate plane.…”
Section: Morphological and Chemical Characterizationmentioning
confidence: 99%
“…Recently, it has been reported that the morphology of CVD silica films deposited by using TEOS as a precursor is largely determined by the existence of these two types of sites and by the presence of memory effects during the growth process [25,26]. Under these conditions the relative concentration of active and passive sites becomes determinant for the film growth.…”
Section: Pr3-136 Journal De Physique IVmentioning
confidence: 99%
“…The chemical vapor deposition (CVD) of tetraethylorthosilicate [TEOS, Si(OC 2 H 5 ) 4 , also known as tetraethoxysilane] and ozone (O 3 ) has been used to deposit SiO 2 films suitable for use in VLSI (very large scale integration) device applications. The TEOS/O 3 reaction system is unique in that the “as deposited” film profile can be varied from a conformal to flowlike step coverage depending on the initial ozone to TEOS concentration ratio. The flowlike property is key to the deposition of high-quality dielectrics for shallow trench isolation with high aspect ratios and finds use in multilevel interconnect devices. Studies have focused on deposition at <400 °C to permit these deposition chemistries to be used with Al and Cu metallization schemes. , …”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] The TEOS/O 3 reaction system is unique in that the "as deposited" film profile can be varied from a conformal to flowlike step coverage depending on the initial ozone to TEOS concentration ratio. [4][5][6][7] The flowlike property is key to the deposition of high-quality dielectrics for shallow trench isolation with high aspect ratios and finds use in multilevel interconnect devices. Studies have focused on deposition at <400 °C to permit these deposition chemistries to be used with Al and Cu metallization schemes.…”
Section: Introductionmentioning
confidence: 99%